An Assessment of the Functional Properties of Black Amaranth Flour During Fermentation with Probiotic Lactic Acid Bacteria - Mamadou Lamarana Souare; Alpha Oumar Sily Diallo; Nicoleta Balan; Mihaela Aida Vasile; Lounceny Traore; Gabriela Elena Bahrim; Mihaela Cotârleț; Caterina Nela Dumitru (Fermentation, 2025)
This study aimed to ferment protein-rich amaranth flour with different strains of lactic acid bacteria (LAB) and to analyse the fermented dough’s functional properties. The fermented dough analysis was conducted using titrimetric, spectrophotometric, and chromatographic methods. The antioxidant activity of the fermented doughs was evaluated using the DPPH (2,2-Diphenyl-1-picrylhydrazyl) and ABTS (2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid)) methods, finding ABTS radical scavenging values ranging from 26.00 ± 1.05% to 58.92 ± 6.05%, while the DPPH values ranged from 21.29 ± 0.83% to 28.24 ± 5.48%. By RP-HPLC (Reversed Phase-High Performance Liquid Chromatography) characterisation, several phenolic acids and flavonoids were identified and quantified. Among these compounds, epigallocatechin was the most abundant, with the highest concentration recorded at 7789.88 ± 17.0 ng/µL in the control sample. This was followed by a 6942.47 ± 5.632 ng/µL concentration in the dough fermented with Lacticaseibacillus rhamnosus MIUG BL38 strain and 4983.16 ± 7.29 ng/µL in the dough fermented with Lactiplantibacillus pentosus MIUG BL24 strain. These two LAB strains (Lc. rhamnosus MIUG BL38 and Lp. pentosus MIUG BL24), with probiotic properties previously demonstrated, were selected based on their acidification potential, antioxidant activity, and bioactivity for future optimisation studies. Lactic acid fermentation significantly enhances bioactive characteristics of the amaranth flour, enabling the design of diverse gluten-free products with increased functional properties based on the attributes induced by the prebiotic, probiotic and postbiotic contents (tribiotics).